Digital Diplomacy And Youth Engagement In Global Change - Khazratkulova Nazokat (International Journal Of History And Political Sciences, 2025)
This paper explores how digital diplomacy is reshaping international relations and empowering youth as active participants in global change. It examines how young people use digital platforms to promote dialogue, peace, and sustainable development, while highlighting barriers such as limited representation and unequal access. Drawing on examples from the EU’s Global Gateway Initiative and Uzbekistan’s Digital Diplomacy Camp, the study argues that digital diplomacy should move beyond communication to collaboration. It proposes creating Digital Diplomacy Labs and youth networks to strengthen digital literacy, combat misinformation, and foster cross-cultural cooperation in Central Asia.